1999
DOI: 10.2355/isijinternational.39.154
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wettability on the Behavior of Argon Bubbles and Fluid Flow inside the Nozzle and Mold.

Abstract: It is well known that the occurrence of the defects has a close relation with the behavior of the bubbles and the flow pattern of the molten steel inside the mold. In this research, the behavior of argon gas inside the flowing water and the influence of wettability between the water and the porous refractory through which argon gas is injected were investigated. In addition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 1 publication
1
23
0
Order By: Relevance
“…Wang et al studied the influence of wettability on the behavior of argon bubbles and fluid flow. 15) Although physical water models are well able to model single-phase fluid flow owing to the simulation kinematic viscosity of steel and water, the flow pattern itself is actually not of greatest interest. Furthermore, the physical bottom used in the water model interferes with the flow, the moving solidifying shell cannot be properly accounted, and properties related to other phenomena such as multiphase flow, heat transfer, and slag entrainment do not have proper similitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al studied the influence of wettability on the behavior of argon bubbles and fluid flow. 15) Although physical water models are well able to model single-phase fluid flow owing to the simulation kinematic viscosity of steel and water, the flow pattern itself is actually not of greatest interest. Furthermore, the physical bottom used in the water model interferes with the flow, the moving solidifying shell cannot be properly accounted, and properties related to other phenomena such as multiphase flow, heat transfer, and slag entrainment do not have proper similitude.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive past work has employed physical water models to successfully investigate fluid flow phenomena in the mold region of the continuous casting process. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The first study was carried out by Afanaseva et al 1) for a straight bore nozzle system. Heaslip et al extensively studied fluid flow in submerged entry nozzles under stopper-rod control and slide-gate control.…”
Section: Introductionmentioning
confidence: 99%
“…These results showed substantially the same tendency as previous studies. [12][13][14] 3. Electrochemical Decomposition of CO 2 Gas in CaCl 2 -CaO Molten Salt…”
Section: Resultsmentioning
confidence: 99%
“…7) An understanding of the behaviors of argon gas and molten steel descending in the immersion nozzle is of practical importance to avoid the pin-hole and sliver defects. Wang et al 8,9) observed the behavior of air descending in a model immersion nozzle made of acrylic pipe. The inner wall of the nozzle was coated with paraffin to make the wettability of the wall be poor.…”
Section: Introductionmentioning
confidence: 99%